Stage-specific disruption of X chromosome expression during spermatogenesis in sterile house mouse hybrids. Issue 2 (2nd December 2021) - Larson, Erica L; Kopania, Emily E K; Hunnicutt, Kelsie E; Vanderpool, Dan; Keeble, Sara; Good, Jeffrey M
Abstract: Hybrid sterility is a complex phenotype that can result from the breakdown of spermatogenesis at multiple developmental stages. Here, we disentangle two proposed hybrid male sterility mechanisms in the house mice, Mus musculus domesticus and M. m. musculus, by comparing patterns of gene expression in sterile F1 hybrids from a reciprocal cross. We found that hybrid males from both cross directions showed disrupted X chromosome expression during prophase of meiosis I consistent with a loss of meiotic sex chromosome inactivation (MSCI) and Prdm9 -associated sterility, but that the degree of disruption was greater in mice with an M. m. musculus X chromosome consistent with previous studies. During postmeiotic development, gene expression on the X chromosome was only disrupted in one cross direction, suggesting that misexpression at this later stage was genotype-specific and not a simple downstream consequence of MSCI disruption which was observed in both reciprocal crosses. Instead, disrupted postmeiotic expression may depend on the magnitude of earlier disrupted MSCI, or the disruption of particular X-linked genes or gene networks. Alternatively, only hybrids with a potential deficit of Sly copies, a Y-linked ampliconic gene family, showed overexpression in postmeiotic cells, consistent with a previously proposed model of antagonistic coevolution between the X- and Y-linked ampliconic genes contributing to disrupted expression late in spermatogenesis. The relative contributions of these two regulatory mechanisms and their impact on sterility phenotypes await further study. Our results further support the hypothesis that X-linked hybrid sterility in house mice has a variable genetic basis, and that genotype-specific disruption of gene regulation contributes to overexpression of the X chromosome at different stages of development. Overall, these findings underscore the critical role of epigenetic regulation of the X chromosome during spermatogenesis and suggest that these processes are prone to disruption in hybrids.